THE CALL OF THE FEMALE MIND – DHALLO - Naik, Vaishali Sanjay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Woman is considered the mother of culture. In the folk literature of every region, the philosophy of women's life is reflected through its various folk songs. The region of Goa is also no exception to this. The folk dances here, Dhallo, Fugdi songs, give a glimpse of Gomantak folk culture. The depiction of the joys and sorrows of women's life is the specialty of these folk songs. 'Dhallo' is a dance festival of women. It is a religious ritual as well as a festival. The ancient folklore scholars of Goa believe that Dhallo is not only a means of entertainment but a religious ritual to honor the mother goddess, a ritual performed for the good of the earth. In this research article, a discussion of the rituals and folk songs of Dhallo is presented.